Philosophical Foundations of Religious Education: Bridging Faith and Reason - Lina aulia; Winda Kurnia Sari; Silvi Yuliana (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
The article investigates the philosophical foundations of religious education and their role in reconciling faith with reason. It critically assesses the relationship between religious belief systems and philosophical inquiry, proposing that religious education should not only transmit religious knowledge but also encourage critical thinking and philosophical reflection on religious matters.